2016
DOI: 10.1002/14651858.cd011684.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for children with ear discharge occurring at least two weeks following grommet (ventilation tube) insertion

Abstract: Interventions for children with ear discharge occurring at least two weeks following grommet (ventilation tube) insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
(1 reference statement)
0
23
0
1
Order By: Relevance
“…The van Dongen et al ’s trial also included secondary outcomes based on parent diaries (patient reported outcome). The authors of this study have previously published evidence demonstrating good agreement between parents and physicians in the assessment of discharge after treatment of acute tympanostomy tube otorrhoea 16. This would imply that the primary outcome used and response rates noted are likely to correlate with everyday clinical practice when otosocopy may not be readily performed.…”
Section: Commentarymentioning
confidence: 82%
“…The van Dongen et al ’s trial also included secondary outcomes based on parent diaries (patient reported outcome). The authors of this study have previously published evidence demonstrating good agreement between parents and physicians in the assessment of discharge after treatment of acute tympanostomy tube otorrhoea 16. This would imply that the primary outcome used and response rates noted are likely to correlate with everyday clinical practice when otosocopy may not be readily performed.…”
Section: Commentarymentioning
confidence: 82%
“…Google and Google Scholar were the only search engines reported. Both search engines were reported in 7 reviews [27][28][29][30][31][32][33] ; Google was reported as the sole search engine in 4 reviews (11 reviews in total) [34][35][36][37] ; Google Scholar was reported as the sole search engine in 12 reviews (19 reviews in total) 25,[38][39][40][41][42][43][44][45][46][47][48] ; and an unnamed search engine was reported in 1 review. 26 Of the 5 reviews that reported the total number of results or the number that was screened, 2 reviews reported the total number of results 27,40 and 3 reviews reported the number that was screened.…”
Section: Additional Details Reported About Search Enginesmentioning
confidence: 99%
“…OME is one of the most common conditions affecting all children. It has been the subject of large number of clinical trials and systematic reviews (Table ) . Accurate incidence and prevalence data are difficult to attain (because OME may be present for short periods then resolve spontaneously).…”
Section: Ent Responsementioning
confidence: 99%
“…Following the water precautions recommended by the surgical team may reduce risk. If the ears do discharge, Jimmy should commence oto‐topical antibiotic drops . Cleaning the pus out of the ear canal may be necessary, so the antibiotic can get to the site of infection.…”
Section: Complications Of Tympanostomy Tubesmentioning
confidence: 99%
See 1 more Smart Citation